Construction of control systems of Mechatron pneumatic devices (Multidisciplinary Journal of Science and Technology, 2024)
Mechatron devices of management pneumatic hydraulic of types used without PLC controller on the side devices automatic process organize to reach see​ we went out Then no results that's it showed that devices quickness in providing manage devices optimization seeing we went out